دور أسلوب التقديم والتأخير في تحسين اللغة العربية - Talqis Nurdiyanto (Arabic Literature Department, 2015)
Manusia dengan tabiatnya memiliki kemampuan berbeda dalam mengelola kosakata dalam bingkai bahasa komunikasinya, terkadang terjadi pembalikan kata bermakna senang disampaikan pada kondisi marah, kata yang seharusnya di awal kalimat diposisikan di tempat lain. Penutur yang menempatkan kata tertentu diawal atau diakhir bukan semata untuk keindahan nada saja, tapi menunjukkan betapa pandainya dalam mengekpresikan keinginannya dengan tingkat seni bahasa yang tinggi. Retorika dalam berbicara dengan gaya bahasa taqdim dan takhir pada kalimatnya memiliki kekuatan makna dan keindahan ungkapan untuk diperhatikan. Meremehkan peran gaya bahasa taqdim dan takhir dapat mengurangi kekuatan makna yang harus dikuatkan dengannya, menghilangkan ruh dan kenikmatan dalam berkomunikasi sehingga ungkapannya terkesan kering jauh dari kaidah bahasa Arab serta gersang dari guyuran fashahah dan balaghah. Stilistika bahasa Arab dalam kerangka ilmu balaghah memiliki peran dalam memperhalus susunan kalimat berbahasa Arab yang rapi dengan balutan makna yang kuat, berpengaruh pada pendengar, mudah dipahami dan tidak rancu tidak alasan untuk menolaknya. Penelitian ini berjudul peran susunan gaya bahasa dengan taqdim dan takhir dalam memperindah bahasa Arab menitikberatkan pada kajian pustaka kebahasa Araban dalam ilmu balaghah. Kalimat yang menggunakan gaya bahasa taqdim dan takhir memiliki arah pada (1) memperindah susunan kalimat dan maknanya, (2) memperindah maknanya saja, (3) memberi makna biasa saja, dan (4) memperancu makna. Kata kunci: uslub, at-taqdîm, at-ta`khîr, tachsîn, al-lughah ‘arabiyyah. AbstractHuman has a natural behavior and different ability to manage vocabularies in the language communication paradigm. Occasionally, the word which has meaning of happy was delivered or spoken by the condition of fury. Based on the language structure, there are some words that actually in the beginning were positioned in the other part. The speakers are using the word in the first or last position in their speech, not only for the aesthetics purposes, but also for the great capability in expressing their desire or purpose using the high level of art. The rhetoric in the speech using the language style of taqdim and takhir in the sentence has a power in meaning and aesthetic expression to be noticed. The underestimate of role in the language style of taqdim and takhir can be reduced the power of meaning that should be strengthened with both styles, and also can effect the lose of soul and enjoyable in the communication act , with the result of that, the expression can be impressioned dryly and by far from the Arabic language grammatical, the splash of fashahah and balaghah. Arabic language stylistics in the Balaghah paradigm has the significant role in managing the structural of senteces smoothly, orderly, using the power of meaning which has the great effect to the audience understandably, not ambiguously, and there is no reason to rejection.This research under the title of “the role of language style structure using taqdim and takhir through Arabic language rethoric and aesthetic was appointed in the literature studies toward Arabic language and Balaghah. The sentences using the language style of taqdim and takhir have many aims, such as: (1) managing the structure and meaning of sentence attractively, (2) just managing only the meaning attractively, (3) giving the meaning commonly, and (4) managing the meaning ambiguously. Keywords: style, taqdim, takhir, aesthetics, Arabic language.Manusia dengan tabiatnya memiliki kemampuan berbeda dalam mengelolakosakata dalam bingkai bahasa komunikasinya, terkadang terjadi pembalikan katabermakna senang disampaikan pada kondisi marah, kata yang seharusnya di awal kalimatdiposisikan di tempat lain. Penutur yang menempatkan kata tertentu diawal atau diakhirbukan semata untuk keindahan nada saja, tapi menunjukkan betapa pandainya dalammengekpresikan keinginannya dengan tingkat seni bahasa yang tinggi. Retorika dalamberbicara dengan gaya bahasa taqdim dan takhir pada kalimatnya memiliki kekuatanmakna dan keindahan ungkapan untuk diperhatikan. Meremehkan peran gaya bahasataqdim dan takhir dapat mengurangi kekuatan makna yang harus dikuatkan dengannya,menghilangkan ruh dan kenikmatan dalam berkomunikasi sehingga ungkapannyaterkesan kering jauh dari kaidah bahasa Arab serta gersang dari guyuran fashahah danbalaghah. Stilistika bahasa Arab dalam kerangka ilmu balaghah memiliki peran dalammemperhalus susunan kalimat berbahasa Arab yang rapi dengan balutan makna yangkuat, berpengaruh pada pendengar, mudah dipahami dan tidak rancu tidak alasan untukmenolaknya. Penelitian ini berjudul peran susunan gaya bahasa dengan taqdim dan takhirdalam memperindah bahasa Arab menitikberatkan pada kajian pustaka kebahasa Arabandalam ilmu balaghah. Kalimat yang menggunakan gaya bahasa taqdim dan takhirmemiliki arah pada (1) memperindah susunan kalimat dan maknanya, (2) memperindahmaknanya saja, (3) memberi makna biasa saja, dan (4) memperancu makna.Kata kunci: uslub, at-taqdîm, at-ta`khîr, tachsîn, al-lughah „arabiyyah.AbstractHuman has a natural behavior and different ability to manage vocabularies in thelanguage communication paradigm. Occasionally, the word which has meaning of happywas delivered or spoken by the condition of fury. Based on the language structure, thereare some words that actually in the beginning were positioned in the other part. Thespeakers are using the word in the first or last position in their speech, not only for theaesthetics purposes, but also for the great capability in expressing their desire or purposeusing the high level of art. The rhetoric in the speech using the language style of taqdimand takhir in the sentence has a power in meaning and aesthetic expression to be noticed.The underestimate of role in the language style of taqdim and takhir can be reduced thepower of meaning that should be strengthened with both styles, and also can effect thelose of soul and enjoyable in the communication act , with the result of that, theexpression can be impressioned dryly and by far from the Arabic language grammatical,the splash of fashahah and balaghah. Arabic language stylistics in the Balaghah paradigmhas the significant role in managing the structural of senteces smoothly, orderly, using theJurnal CMES Volume VIII Nomor 1 Edisi Januari – Juni 2015Program Studi Sastra Arab FIB UNS Surakarta5power of meaning which has the great effect to the audience understandably, notambiguously, and there is no reason to rejection. This research under the title of ―the roleof language style structure using taqdim and takhir through Arabic language rethoric andaesthetic was appointed in the literature studies toward Arabic language and Balaghah.The sentences using the language style of taqdim and takhir have many aims, such as: (1)managing the structure and meaning of sentence attractively, (2) just managing only themeaning attractively, (3) giving the meaning commonly, and (4) managing the meaningambiguously.Keywords: style, taqdim, takhir, aesthetics, Arabic lan